2022
DOI: 10.3390/molecules28010013
|View full text |Cite
|
Sign up to set email alerts
|

Study on Volatile Chemicals as Spoilage Indexes of Salmon by HS-SPME-GC-MS Technique during Non-Frozen Storage

Abstract: Freshness is the most fundamental and important factor to assess raw fish quality. The purpose of our study was to determine the potential spoilage indexes of salmon during non-frozen storage by using headspace solid-phase microextraction (HS-SPME) followed by gas chromatography-mass spectrometry (GC-MS). More than 300 volatile compounds in salmon were detected when sensory scores declined gradually following the quality changes of salmon at different temperatures. And there were 27 and 31 compounds that showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…In contrast, Xuan et al. (2023) observed that 1‐penten‐3‐ol reduced in raw salmon during an 80‐h storage at 4°C and 25°C. The contrary results can be explained by the different type of fish, temperature, and duration of storage (Martin et al., 2023).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In contrast, Xuan et al. (2023) observed that 1‐penten‐3‐ol reduced in raw salmon during an 80‐h storage at 4°C and 25°C. The contrary results can be explained by the different type of fish, temperature, and duration of storage (Martin et al., 2023).…”
Section: Resultsmentioning
confidence: 89%
“…It has been reported that 1-penten-3-ol can be used as a marker of lipid oxidation in chilled Atlantic horse mackerel and fillet of European Seabass as well as Atlantic Salmon (Iglesias & Medina, 2008;Kritikos et al, 2020). In contrast, Xuan et al (2023) observed that 1-penten-3-ol reduced in raw salmon during an 80-h storage at 4 • C and 25 • C. The contrary results can be explained by the different type of fish, temperature, and duration of storage (Martin et al, 2023). Cheng et al (2023) observed a different profile of volatile compounds for tilapia (Oreochromis mossambicus) fillet during a 15-day cold storage at 4 • C, in which octane, 2-nonone, isovaleraldehyde, dimethyl sulfide, and indolizine were primarily responsible for the fillet odor.…”
Section: Changes Of Volatile Compoundsmentioning
confidence: 99%